THE EFFECT OF ECONOMIC GROWTH AND LABOUR ABSORPTION ON POVERTY RATE IN MALUKU PROVINCE 2007-2021 - SHERLY FERDINANDUS; VENTJE JEFFRY KUHUPARUW (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
This study aims to analyse: The Effect of Economic Growth on Poverty Level in Maluku Province; The Effect of Labour Absorption on Poverty Level in Maluku Province; The Effect of Economic Growth and Labour Absorption on Poverty Level in Maluku Province This study uses time series data. Which starts from 2007 to 2021. Data analysis uses multiple regression analysis. The results showed that partially and simultaneously economic growth and labour absorption had an influence on the poverty rate in Maluku Province.